2020
DOI: 10.1177/2192568220948035
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus—A Risk Factor for the Development of Lumbar Disc Degeneration: A Retrospective Study of an Indian Population

Abstract: Study Design: A retrospective study. Objectives: To determine the association between type-2 diabetes mellitus (T2DM) and the severity of lumbar disc degeneration disease (LDDD). Methods: We included 199 patients with low back pain (LBP) who visited our hospital from 2016 to 2018. All patients were divided into 3 groups as per inclusion criteria. Group A, patients without DM (n = 75); group B, patients with controlled DM (n = 72); and group C, patients with uncontrolled DM (n = 52). The patients were further s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
(24 reference statements)
1
1
0
Order By: Relevance
“…In line with other studies, 6 , 10 , 11 we found intervertebral disc degeneration and degenerative spondylolisthesis as being disproportionally more frequent indications for primary spinal fusion surgery in patients with diabetes than was expected from the prevalence of this disease in the studied population. In this study, we showed that spine degenerative conditions are major contributors to the development of ASD in diabetic individuals requiring revision surgery (RR = 2.26; 95% CI, 1.45–3.53).…”
Section: Discussionsupporting
confidence: 92%
“…In line with other studies, 6 , 10 , 11 we found intervertebral disc degeneration and degenerative spondylolisthesis as being disproportionally more frequent indications for primary spinal fusion surgery in patients with diabetes than was expected from the prevalence of this disease in the studied population. In this study, we showed that spine degenerative conditions are major contributors to the development of ASD in diabetic individuals requiring revision surgery (RR = 2.26; 95% CI, 1.45–3.53).…”
Section: Discussionsupporting
confidence: 92%
“…7 SPPs and NSHCs are concurrently listed in the global top 20 leading causes of years lived with disability, inflicting enormous health and financial tolls on individuals and society. 2 3 Associations have been reported between SPPs and NSHCs, including mental health disorders, [8][9][10][11] diabetes, [11][12][13][14] obesity 15 and various musculoskeletal conditions. 16 17 Such associations are important to consider because they may complicate the clinical management of patients and they are related to lower quality of life, poorer functional status and increased utilisation of healthcare.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The etiology of IDD is multifactorial and not completely elucidated. To date, multiple factors have been recognized involved in the progression of IDD, such as ageing, smoking, diabetes mellitus (DM), obesity, abnormal mechanical load and genetic predisposition ( Figure 1 ) ( Kim et al, 2009 ; Le Maitre et al, 2007 ; Jeong et al, 2014 ; Desmoulin et al, 2020 ; Maclean et al, 2004 ; Walsh and Lotz, 2004 ; Wuertz et al, 2009 ; Kalb et al, 2012 ; Martirosyan et al, 2016 ; Alpantaki et al, 2019 ; Kakadiya et al, 2020 ; Livshits et al, 2001 ; Chen et al, 2018 ; Cannata et al, 2020 ). In response to those risk factors, various crucial pathological processes develop, including the loss of resident IVD cells, ECM remodeling, inflammation and oxidative stress ( Figure 1 ) ( Gruber and Hanley, 1998 ; Nasto et al, 2013 ; Suzuki et al, 2015 ; Lyu et al, 2021 ).…”
Section: Pathological Mechanism Of Intervertebral Disc Degenerationmentioning
confidence: 99%